2022
DOI: 10.1590/pboci.2022.057
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Knowledge on Emergency Management of Avulsed Teeth Among Turkish Medical and Dental Students

Abstract: How to cite: Duruk G, Daşkıran IC. Evaluation of knowledge on emergency management of avulsed teeth among Turkish medical and dental students. Pesqui Bras Odontopediatria Clín Integr. 2022; 22:e210092.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
(50 reference statements)
0
3
0
Order By: Relevance
“…14,15 There are few studies evaluating the level of knowledge of medical students about dental trauma. 8,9,[16][17][18] This study provided basic information about the current level of knowledge of senior-year medical students about dental avulsion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14,15 There are few studies evaluating the level of knowledge of medical students about dental trauma. 8,9,[16][17][18] This study provided basic information about the current level of knowledge of senior-year medical students about dental avulsion.…”
Section: Discussionmentioning
confidence: 99%
“…There are studies in the literature 8,9 with similar results to our study. In the study conducted by Duruk et al 17 the knowledge levels of preclinical dentistry students, clinical dentistry students, medical students, and medical students who were given 1 hour of training on dental trauma about emergency management of avulsed teeth were investigated. In this study, it was concluded that medical and preclinical dentistry students lacked knowledge about emergency management of avulsed teeth, while clinical dentistry and trained medical students were very knowledgeable.…”
Section: Discussionmentioning
confidence: 99%
“…Encourage them to take part in dentistry camps and other TDI-related courses, which can help them learn more about trauma cases and boost their confidence in handling them. [25] Al-Shamiri et al [26] concluded that dental students lacked adequate knowledge of dental trauma management and suggested a number of instructional strategies, including problem-based learning and bolstering the curriculum on those subjects, to help them learn more. A study by Aboubakar et al [27] found that Saudi and Egyptian dental interns had adequate levels of knowledge about the majority of topics related to managing tooth avulsions and that dental interns with experience of more than six months and prior knowledge of managing avulsed teeth performed better when answering questions.…”
Section: Discussionmentioning
confidence: 99%